The impact of digital financial inclusion on the high-quality development of pastoral economy in China’s minority regions - Wang, Jun; Zhang, Xinyi; Du, Yuting; Deng, Yingying; Cao, Jianmin; Liang, Yuan (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn the pursuit of high-quality development in the pastoral economy, digital financial inclusion (DFI) plays an indispensable role in driving progress. The system of DFI constructed through “digital technology + inclusive finance” has gradually extended various financial services, such as lending and financing, to the pastoral areas of ethnic minorities, significantly reducing the barriers and costs for herdsmen to access financial services.MethodsBased on the panel data of 26 prefecture-level cities in the 9 main pastoral provinces of ethnic minorities in China from 2011 to 2022, this paper employs the entropy weight method to construct a High-Quality Development Index for animal husbandry. Utilizing fixed-effects and mediation-effect models, we analyze and elucidate the pivotal role of DFI in promoting the high-quality development of animal husbandry in impoverished regions, with particular emphasis on its underlying mechanisms.Results(1) DFI has a significant positive effect on the high-quality development of the pastoral economy in China’s ethnic minority pastoral areas. Mechanism tests reveal that DFI promotes high-quality development in these regions through increased output value and income. (2) Structural heterogeneity analysis reveals that the coverage and usage depth of DFI have a significant positive effect on the high-quality development of the pastoral economy in ethnic minority pastoral areas. (3) Mediation effect tests indicate that DFI can further promote the high-quality development of the pastoral economy through the trickle-down effect of non-agricultural employment and the optimization of the pastoral industry structure.DiscussionThis study provides theoretical support and empirical evidence for promoting the high-quality development of the pastoral economy through DFI. It also offers micro-level evidence for alleviating the funding constraints of herdsmen in remote areas without collateral through DFI.